(untitled) (Pashupati Pragya पशुपति प्रज्ञा, 2026)
The study examines how Robin Sharma’s The Monk Who Sold His Ferrari highlights ‘inner transformation’ as a source of happiness which is obtained through the principle of detachment that falls under the rubrics of Buddhism. The core concepts like self-awakening and spiritual salvation, inner mindfulness, and self-discipline insights of Buddhist teachings which are integrated in the life of Julian Mantle who undergoes a massive transformation from material oriented man to spiritual one. His metamorphosis from material success toward a life of simple calm life mirroring Buddhist thoughts shows how The Monk Who Sold His Ferrari integrates Buddhist inner thinking to life a blessed life detached from greed and bodily pleasure. The central issue of this research seeks to understandthe real source of happiness and find the actual difference between material success and spiritual dimension of life leading to self-awakening. The implication behind figuring out spiritual happiness is foreground the idea that source of happiness does not lie in the unstable material objects but rather in transcending them.